RESPONSIBILITY OF BUSINESS ACTORS FOR THE TRANSFER OF CONSUMER CHANGE FORMS - I Made Ananda Dwirama Wiguna; Dewa Gede Pradnyana Yustiawan (Transpublika Publisher, 2023)
This article aims to provide an understanding of the legal arrangements for the transfer of consumer change forms by business actors and examine the responsibility of business actors for the transfer of consumer change forms that can result in losses to consumers. The writing of this article uses a normative legal research method through a statutory approach, conceptual approach, case approach and use primary and secondary legal materials. The characteristics of this research are categorized as descriptive research. The results of the study show that the regulation regarding the transfer of consumer change is regulated in Law no. 8 of 1999 concerning Consumer Protection, Law no. 23 of 1999 and Law no. 7 of 2011 which basically stipulates that rupiah currency is a legal tender in the territory of the Republic of Indonesia so that consumer change must be in the form of rupiah currency without being transferred in any form. This will certainly cause deviations in terms of legal rules because consumers feel disadvantaged and violated their rights. Therefore, a legal review is needed based on related regulations, especially regarding the responsibility of business actors for the transfer of consumer change.